2011
DOI: 10.1016/j.mce.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin in Type 2 diabetes mellitus and metabolic syndrome

Abstract: Please cite this article as: Ukkola, O., Ghrelin in type 2 diabetes mellitus and metabolic syndrome, Molecular and Cellular Endocrinology (2010),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
4
27
1
1
Order By: Relevance
“…We found that ghrelin concentrations of patients with type 2 diabetes was significantly lower (P<0.05) than those of controls group which was in line with previous studies [7,[15][16][17]. Our findings support the view that low ghrelin level could have a causative role in the development of type 2 diabetes.…”
Section: Ghrelin Concentrations In the Studied Groupssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that ghrelin concentrations of patients with type 2 diabetes was significantly lower (P<0.05) than those of controls group which was in line with previous studies [7,[15][16][17]. Our findings support the view that low ghrelin level could have a causative role in the development of type 2 diabetes.…”
Section: Ghrelin Concentrations In the Studied Groupssupporting
confidence: 92%
“…The majority of the publications addressing the relationship between ghrelin and insulin resistance and/or diabetic states suggest that a correlation between ghrelin and insulin resistance and/or diabetes might exist [5][6][7]. A recent study showed that a high circulating ghrelin level was associated with insulin resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hypersecretion of ghrelin caused by a lack of insulin effects can lead to diabetic polyphagia. This in turn can lead to the development of several metabolic abnormalities that include obesity and cardiovascular complications (Duckworth, 2001;Ukkola, 2011). Therefore, increased food intake ascribed to elevated plasma ghrelin concentrations is a major contributor to the development of macro-and microvascular complications of diabetes (Shintani et al, 2001;Ukkola, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn can lead to the development of several metabolic abnormalities that include obesity and cardiovascular complications (Duckworth, 2001;Ukkola, 2011). Therefore, increased food intake ascribed to elevated plasma ghrelin concentrations is a major contributor to the development of macro-and microvascular complications of diabetes (Shintani et al, 2001;Ukkola, 2011). Additionally, enhanced plasma ghrelin levels have also been observed in rats with streptozotocin-induced diabetes and are associated with diabetic polyphagia (Delhanty & van der Lely, 2011;Masaoka et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in normal physiology, ghrelin has been associated with a number of disease processes, including obesity (Scerif et al 2011, Yi et al 2011, type 2 diabetes mellitus and hyperinsulinaemia (Ukkola 2011), gastrointestinal disease (Jeffery et al 2011), cardiovascular disease (Isgaard & Granata 2011), reproductive disorders (Repaci et al 2011), mental health (Steiger et al 2011) and cancer (Chopin et al 2011, Deboer 2011. Ghrelin may play a role in prostate cancer progression, and we have previously demonstrated that ghrelin mRNA and protein is expressed in prostate cancer cell lines and tissues and that ghrelin stimulates cell proliferation in prostate cancer cell lines (Jeffery et al 2002.…”
Section: Introductionmentioning
confidence: 99%